Purriato is a conserved small open reading frame gene that interacts with the CASA pathway to regulate muscle homeostasis and epithelial tissue growth in Drosophila - Pueyo, Jose I.; Salazar, Jorge; Grincho, Carolina; Berni, Jimena; Towler, Benjamin P.; Newbury, Sarah F. (Frontiers in Cell and Developmental Biology, 2023)
Recent advances in proteogenomic techniques and bioinformatic pipelines have permitted the detection of thousands of translated small Open Reading Frames (smORFs), which contain less than 100 codons, in eukaryotic genomes. Hundreds of these actively translated smORFs display conserved sequence, structure and evolutionary signatures indicating that the translated peptides could fulfil important biological roles. Despite their abundance, only tens of smORF genes have been fully characterised; these act mainly as regulators of canonical proteins involved in essential cellular processes. Importantly, some of these smORFs display conserved functions with their mutations being associated with pathogenesis. Thus, investigating smORF roles in Drosophila will not only expand our understanding of their functions but it may have an impact in human health. Here we describe the function of a novel and essential Drosophila smORF gene named purriato (prto). prto belongs to an ancient gene family whose members have expanded throughout the Protostomia clade. prto encodes a transmembrane peptide which is localized in endo-lysosomes and perinuclear and plasma membranes. prto is dynamically expressed in mesodermal tissues and imaginal discs. Targeted prto knockdown (KD) in these organs results in changes in nuclear morphology and endo-lysosomal distributions correlating with the loss of sarcomeric homeostasis in muscles and reduction of mitosis in wing discs. Consequently, prto KD mutants display severe reduction of motility, and shorter wings. Finally, our genetic interaction experiments show that prto function is closely associated to the CASA pathway, a conserved mechanism involved in turnover of mis-folded proteins and linked to muscle dystrophies and neurodegenerative diseases. Thus, this study shows the relevance of smORFs in regulating important cellular functions and supports the systematic characterisation of this class of genes to understand their functions and evolution.